Recent evolution of minorities’ attendance and profile at Universidade Federal de Minas Gerais - Golgher, André Braz (2021)
In order to decrease attendance inequalities at the tertiary level in Brazil, affirmative action policies were implemented, including the bonus and quotas policies at Universidade Federal de Minas Gerais (UFMG). Besides, the Programa de Apoio a Planos de Reestruturação e Expansão das Universidades (Reuni) and the use of Exame Nacional do Ensino Médio/Sistema de Seleção Unificado (Enem/SiSU) in the selection process may have affected the proportion of minorities in public higher education institutions in Brazil. The paper’s main objective is to verify the evolution of the student body diversity at UFMG between 2006 and 2015, addressing the effects of these changes. The Reuni, bonus and quota policies seemed to be effective in decreasing inequalities of different sorts at UFMG, while Enem/ SiSU promoted an increased in attendance’s inequality. Moreover, the determinants of the propensity of belonging to low-income households, being Black/Pardo or from private or state secondary schools were assessed.